The Impact of Participatory and Familial Leadership on Employee Performance in Religious Service Organizations - M Shonhaji; Adityo Nugroho; Herdian Farisi (Journal of Economic and Business Analysis, 2024)
This study analyzes the leadership style of the Head of the Religious Affairs Office (KUA) in Bukateja District, Purbalingga, and its impact on employee performance. Using a descriptive qualitative method, data were collected through in-depth interviews, observations, and document reviews. The results showed that the Head of KUA used a participatory and familial leadership style. Decision making was carried out through consensus, and assignments were based on employee competence. Feedback was provided through periodic evaluations, and reprimands were given privately to maintain harmonious working relationships. Although there were no material rewards, employees showed high dedication, driven by a supportive work environment and empathetic leadership. This study underlines the effectiveness of inclusive leadership in encouraging optimal performance in faith-based organizations. This study recommends the implementation of non-material rewards and additional leadership training to improve employee motivation. Further research in similar institutions is recommended to explore variations in leadership styles.